(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study compared the creatinine-to-cystatin C ratio and examined its associations with metabolic characteristics and renal function in patients with and without acute hyperglycemia. Methods: A case-control study was conducted in 76 outpatients with type 2 diabetes mellitus, including 38 patients with acute hyperglycemia (fasting glucose ≥ 180 mg/dL) and 38 patients age- and sex-matched stable controls. Variables included BMI, fasting glucose, HbA1c, serum creatinine, cystatin C, and urinary albumin-to-creatinine ratio. Estimated glomerular filtration rate (GFR) was calculated using the CKD-EPI (2021) creatinine equation and the CKD-EPI (2012) cystatin C equation. Pearson or Spearman correlation analyses were performed. Results: The hyperglycemia group had higher BMI, HbA1c, creatinine, urinary albumin-to-creatinine ratio, and creatinine-to-cystatin C ratio, but lower cystatin C (p < 0.001). eGFR-Cre decreased, whereas eGFR-Cys increased compared with controls (p < 0.001). The creatinine-to-cystatin C ratio reversed its correlation with BMI between groups and was no longer associated with HbA1c or eGFR-Cre in the hyperglycemia group. Conclusions: Acute hyperglycemia is associated with discordance between creatinine and cystatin C. The creatinine-to-cystatin C ratio may serve as an adjunctive marker for renal function assessment during acute metabolic stress.